BOOSTING STUDENT INVOLVEMENT WITH ACTIVE LEARNING TECHNIQUES IN HIGHER EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the influence of active learning strategies on academic performance and student engagement. This article employed a methodology that integrates quantitative surveys and qualitative interviews to inestigate the effects of active learning in greater detail. The findings suggest a significant increase in student engagement and motivation, as well as an improvement in academic performance and participation in class activities. The essential information underscores that students appreciate the interactive nature of effective teaching methods, such as collaborative projects and group discussions, despite the presence of certain challenges associated with the transition from passive to active learning and time management. This study examines the advantages of active learning and offers potential solutions to the challenges that educators may encounter when attempting to implement these \techniques in the classroom.